The Three Legged Cat - Mahy, Margaret; Allen, Jonathan, 1957- (New York : Viking, 1993)
Mistaken identity means all their dreams come true when Mrs. Gimbles roving brother pays her and her three-legged cat his annual visit. Suggested level: preschool, junior.
"Ages 3-8"--Jkt.
Keywords: Cats -- Juvenile fiction; Humorous fiction; Fiction; Juvenile works; Humorous fiction